The influence of obesity and body mass index on the outcome of laparoscopic colorectal surgery: a systematic literature review. (October 2016) - Hotouras, A.; Ribas, Y.; Zakeri, S. A.; Nunes, Q. M.; Murphy, J.; Bhan, C.; Wexner, S. D.
Abstract: Aim: The relationship between obesity, body mass index (BMI) and laparoscopic colorectal resection is unclear. Our object was to assess systematically the available evidence to establish the influence of obesity and BMI on the outcome of laparoscopic colorectal resection. Method: A search of PubMed/Medline databases was performed in May 2015 to identify all studies investigating the impact of BMI and obesity on elective laparoscopic colorectal resection performed for benign or malignant bowel disease. Clinical end‐points examined included operation time, conversion rate to open surgery, postoperative complications including anastomotic leakage, length of hospital stay, readmission rate, reoperation rate and mortality. For patients who underwent an operation for cancer, the harvested number of lymph nodes and long‐term oncological data were also examined. Results: Forty‐five studies were analysed, the majority of which were level IV with only four level III (Oxford Centre for Evidence‐based Medicine 2011) case‐controlled studies. Thirty comparative studies containing 23 649 patients including 17 895 non‐obese and 5754 obese showed no significant differences between the two groups with respect to intra‐operative blood loss, overall postoperative morbidity, anastomotic leakage, reoperation rate, mortality and the number of retrieved lymph nodes in patients operated on for malignancy. Most studies, including 15 non‐comparative studies, reported a longer operation time in patients who underwent a laparoscopic procedure with the BMI being an independent predictor in multivariate analyses for the operation time. Conclusion: Laparoscopic colorectal resection is safe and technically and oncologically feasible in obese patients. These results, however, may vary outside of high volume centres of expertise.